Effect of feeding palm kernel cake fermented by fiber degrading bacteria on performance of broiler chicken - Alshelmani, Mohamed M Idris (2015)
Malaysia has an abundant amount of palm kernel cake (PKC), which is considered to be an agro-industrial waste after the extraction process of oil from palm fruits. The challenge of using the PKC in the poultry diet is the presence of the high levels of fibers. were conducted to investigate the effect of palm kernel cake fermented Based on the limitation and importance of using the PKC in broiler diets, it appears to be necessary to improve the nutritive value of this by-product by solid state fermentation (SSF) using fiber degrading bacteria. Therefore, four experiments by cellulolytic bacteria (FPKC) on the performance of broiler. The objectives of the first two experiments were to characterize the cellulolytic bacteria in terms of their properties of producing cellulolytic enzymes; in addition, to improve the nutritive value of the PKC via SSF. In addition, a digestibility trial was conducted to investigate the effect of FPKC on crude protein (CP) and amino acids (AA) digestibility on broiler chickens. The fourth experiment was carried out to study the effect of FPKC on broiler growth performance, carcass and meat quality, nutrient digestibility, villi height, gut microflora and blood biochemistry. In the first experiment, nine cellulolytic bacteria were characterized in different substrates; carboxymethyl cellulose (CMC) or xylan from birchwood or locus bean gum (LBG) galactomannan. Results showed that Bacillus amyloliquefaciens DSMZ 1067, Bacillus megaterium ATCC 9885, Paenibacillus curdlanolyticus DSMZ 10248, and Paenibacillus polymyxa ATCC 842 produced higher enzymes activities compared to the other bacterial cultures grown in different substrates. In the second experiment, the PKC was undergone SSF by the four cellulolytic bacteria mentioned earlier. The findings observed that bacterial cultures produced high enzymes activities at the 4th day of SSF, and decreased to zero at the 8th day of SSF. Moreover, the fiber contents were significantly decreased (P< 0.05) and the reducing sugars were significantly increased (P< 0.05) in FPKC compared with untreated PKC. In the third experiment, a total of 24 broiler chickens were randomly distributed into three treatments: untreated PKC, FPKCa by P. polymyxa ATCC 842 and FPKCb by P. curdlanolyticus DSMZ 10248. The findings showed that of CP was increased from 16.47% in the untreated PKC to 16.68% and 16.80% in FPKCa and FPKCb, respectively. In addition, the apparent ileal digestibility (AID) of CP and glutamate were significantly (P< 0.05) increased in FPKCa compared to the untreated PKC. The rest of AA digestibility were increased in FPKC but not significantly different (P> 0.05). In the fourth experiment, a total of 245 one-day-old broiler chicks were randomly distributed to seven dietary treatments containing 0, 5, 10 and 15% PKC and 5, 10 15% FPKC by P. polymyxa ATCC 842. The results showed that the addition of 10 or 15% PKC in broiler diets led to a significant (P<0.05) decrease in the growth performance and nutrient digestibility. However, it was significantly (P<0.05) improved in groups of chickens fed with 10 or 15% FPKC compared with those fed with 10 or 15% PKC. The relative weight of the gizzard was significantly (P< 0.05) higher for the broiler group fed with 15% PKC compared to those birds fed with the negative control or FPKC at three weeks of age. No significant (P> 0.05) differences were observed between the dietary treatments in terms of meat quality, blood biochemistry, villi height and internal organs. Nevertheless, gut microflora were significantly improved (P< 0.05) in birds fed with 15% FPKC compared to the other dietary treatments. In conclusion, PKC fermented by P. polymyxa ATCC 842 could be fed to broiler chickens up to 15% in their rations without any adverse effects on their growth performance.